Seasonal Incidence of Insect-pests in Tomato (Lycopersicon esculantum M.) on Different Planting Dates and its Correlation with Abiotic Factors - Waluniba; Ao, M. Alemla (International Journal of Bio-resource and Stress Management, 2023)
Experiment conducted in the year 2010-2011 at experimental cum research farm, School of Agriculture Sciences and Rural Development, Nagaland University, showed that the incidence of aphids (Aphis gossypii) was observed at 52nd, 2nd and 4th, whitefly (Bemisia tabaci) at 4th, 7th and 9th, Serpentine leaf miner (Liriomyza trifolii) at 4th, 7th and 9th and fruit borer (Helicoverpa armigera) at 9th, 11th and 13th standard week on D1, D2 and D3 respectively. The incidence of aphid correlating with abiotic factors showed negative significant influence by maximum temperature at 4th December planting date, whitefly showed negative significant influence on 4th December planting date, leaf miner showed positive significant effect with maximum and minimum temperature in all the planting dates and also minimum relative humidity on 19th December planting showed positive significant effect and in case of tomato fruit borer it showed a positive significant effect with maximum temperature and minimum relative humidity at 19th November and 19th December planting respectively.